SUITABILITY OF COASTAL ECOTOURISM IN PADANG CITY - WEST SUMATERA: CASE STUDY OF BEACH RECREATION AND MANGROVE - Aprizon Putra; Try Al Tanto; Widodo S Pranowo; Ilham Ilham; Harfiandri Damanhuri; Yurni Suasti; Triyatno Triyatno (Jurnal Segara, 2018)
The coastline length of Padang city is about 80 km with area 72,000 ha of coastal waters and 19 small islands. Overall, the beach of Padang City consists of the sloping beach (41.52 km), cliff (22.08 km), muddy beach (8.19 km), and also an artificial beach for coastal protection. The research aims to identify the beach that is suitable for coastal ecotourism, including those of beach recreation and mangrove areas. The methodology that was used was to estimate the Ecotourism Suitability Index (ESI) based on weighting and scoring of some physical parameters. The research results for suitability category of recreational beach in Padang City show 18 locations are suitable very (with average 82,28 %), 8 locations are suitable enough (with average 70 %), and only one beach location in front of Bung Hatta University is in conditional category (27 %). The beach suitable for mangrove ecotourism is identified in 6 locations are suitable very (with average 92 %), 9 locations are suitable enough (with average 73 %), 3 locations are suitable conditional (with average 49 %), while those which are not suitable in Carolina (Pasa Laban) beach (33 %).